Coalition warfare : an anthology of scholarly presentations at the Conference on Coalition Warfare at the Royal Danish Defence College, 2011 /: an anthology of scholarly presentations at the Conference on Coalition Warfare at the Royal Danish Defence College, 2011. (2013) - Unknown
No abstract available